Effect of Oxidation Temperature on Physical and Electrical Properties of Sm2O3 Thin-Film Gate Oxide on Si Substrate - Goh, K.H.; Haseeb, A.S. Md. Abdul; Wong, Y.H. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Thermal oxidation of 150-nm sputtered pure samarium metal film on silicon substrate has been carried out in oxygen ambient at various temperatures (600°C to 900°C) for 15 min and the effect of the oxidation temperature on the structural, chemical, and electrical properties of the resulting Sm2O3 layers investigated. The crystallinity of the Sm2O3 films and the existence of an interfacial layer were evaluated by x-ray diffraction (XRD) analysis, Fourier-transform infrared (FTIR) spectroscopy, and Raman analysis. The crystallite size and microstrain of Sm2O3 were estimated by Williamson–Hall (W–H) plot analysis, with comparison of the former with the crystallite size of Sm2O3 as calculated using the Scherrer equation. High-resolution transmission electron microscopy (HRTEM) with energy-dispersive x-ray (EDX) spectroscopy analysis was carried out to investigate the cross-sectional morphology and chemical distribution of selected regions. The activation energy or growth rate of each stacked layer was calculated from Arrhenius plots. The surface roughness and topography of the Sm2O3 layers were examined by atomic force microscopy (AFM) analysis. A physical model based on semipolycrystalline nature of the interfacial layer is suggested and explained. Results supporting such a model were obtained by FTIR, XRD, Raman, EDX, and HRTEM analyses. Electrical characterization revealed that oxidation temperature at 700°C yielded the highest breakdown voltage, lowest leakage current density, and highest barrier height value.